2003
DOI: 10.1023/b:phot.0000027515.05641.fd
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of Two Distinct Plant Species, Spring Barley and Norway Spruce, to Combined Effect of Various Irradiance and CO<sub>2</sub> Concentration During Cultivation in Controlled Environment

Abstract: The short-term acclimation (10-d) of Norway spruce [Picea abies (L.) Karst] to elevated CO 2 concentration (EC) in combination with low irradiance (100 µmol m -2 s -1 ) resulted in stimulation of CO 2 assimilation (by 61 %), increased total chlorophyll (Chl) content (by 17 %), significantly higher photosystem 2 (PS2) photochemical efficiency (F v /F m ; by 4 %), and reduced demand on non-radiative dissipation of absorbed excitation energy corresponding with enhanced capacity of photon utilisation within PS2. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
(59 reference statements)
3
18
0
Order By: Relevance
“…We suggest that this difference of the spectral composition may both affect light harvesting in the different parts of canopy during the sunny days and contribute to the signals driving synthesis and/or degradation of light harvesting complexes. As shown earlier for Norway spruce needles the Chl a/b ratio rapidly changes during the transfer of a plant from the understorey of the canopy to the direct solar radiation (Š punda et al 1993), but sometimes Chl a/b ratio is not affected during acclimation of low irradiance (100 lmol m -2 s -1 ) plants to high irradiance (1,200 lmol m -2 s -1 ) conditions (Kurasová et al 2003). The latter case was reported particularly for the plants acclimated in the growth chambers, where the spectral composition of low irradiance is the same as that of high irradiance.…”
Section: The Diurnal Dynamics Of the Spectral Composition Of Parmentioning
confidence: 69%
“…We suggest that this difference of the spectral composition may both affect light harvesting in the different parts of canopy during the sunny days and contribute to the signals driving synthesis and/or degradation of light harvesting complexes. As shown earlier for Norway spruce needles the Chl a/b ratio rapidly changes during the transfer of a plant from the understorey of the canopy to the direct solar radiation (Š punda et al 1993), but sometimes Chl a/b ratio is not affected during acclimation of low irradiance (100 lmol m -2 s -1 ) plants to high irradiance (1,200 lmol m -2 s -1 ) conditions (Kurasová et al 2003). The latter case was reported particularly for the plants acclimated in the growth chambers, where the spectral composition of low irradiance is the same as that of high irradiance.…”
Section: The Diurnal Dynamics Of the Spectral Composition Of Parmentioning
confidence: 69%
“…Chl a/b and Chl a+b/Car x+c were estimated spectrophotometrically (UV/VIS 550, Unicam, England) from pigment extracts in 80% acetone with a small amount of MgCO 3 according to Lichtenthaler (1987). The VAZ content expressed per projected needle area was estimated via gradient reversed-phase high-performance liquid chromatography (TSP Analytical, USA) according to Färber and Jahns (1998) with a minor modification (Kurasová et al, 2003). The details have been described in our previous work (Štroch et al, 2008a).…”
Section: Photosynthetic Pigment Analysismentioning
confidence: 99%
“…Analyses were carried out with gradient pump (Spectra Series P4000) and the autosampler AS3000 with 50 ll sample loop (both TSP Analytical, USA). The detailed description is given in our previous report [24]. The middle segments of 2 h dark-adapted leaves were used for the pigment analysis.…”
Section: Pigment Analysismentioning
confidence: 99%
“…It has been suggested that the sustained Z + A may be involved in protective (Z + A)-dependent energy dissipation [24,49]. The retention of Z + A is usually accompanied with the suppressed F V =F M [8,50].…”
Section: Specific Features Of the Clo F2 Mutant Response To Hlmentioning
confidence: 99%